THE USE OF PEDAGOGICAL GAMES IN THE PRACTICAL ORGANIZATION OF MATHEMATICS BY PRIMARY SCHOOL TEACHERS - Хамидова Шахло; Абдухалилова Дилафруз (TADQIQOTLAR.UZ, 2024)
Abstract: This article describes in detail the teaching of mathematics in elementary classes, which is considered a small and important part of the school, and the improvement of the effectiveness of lessons through the practical use of modern pedagogical technologies.